Anti-infective and herbicidal activity of N-substituted 2-aminobenzothiazoles - Fajkusova, Dagmar; Pesko, Matus; Keltosova, Stanislava; Guo, Jiahui; Oktábec, Zbyněk; Vejsova, Marcela; Kollar, Peter; Coffey, Aidan; Csollei, Jozef; Kralova, Katarina; Jampilek, Josef (Bioorganic & medicinal chemistry, 2012)
In this study, a series of N-substituted 2-aminobenzothiazoles was prepared according to a recently developed method. Twelve compounds were tested for their activity related to the inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. Primary in vitro screening of the discussed compounds was also performed against fungal, bacterial and mycobacterial species. The biological activities of some compounds were comparable or higher than the standards phenoxymethylpenicillin or pyrazinamide. The most effective compounds demonstrated insignificant toxicity against the human monocytic leukemia THP-1 cell line. For all compounds, the structure-activity relationships are discussed.
Keywords: nádorové buněčné linie; Cell Line, Tumor; Humans; Microbial Sensitivity Tests; Benzothiazoles; Anti-Infective Agents; protinádorové látky; Chloroplasts; Drug Screening Assays, Antitumor; Structure-Activity Relationship; herbicidy; Antifungal Agents; antifungální látky; benzothiazoly; vztahy mezi strukturou a aktivitou; Antineoplastic Agents; lidé; mikrobiální testy citlivosti; screeningové testy protinádorových léčiv; Spinacia oleracea; chloroplasty; Herbicides; antiinfekční látky